-0.2x^2 + 12x +11 = 0

here is what I have done

-(12) + or - sqrt 12^2-4(-0.2)(11)/2(-0.2)

-12 + or - sqrt 144 +8.8/-0.4

-12 + or - sqrt 152.2/-0.4

at this point I am lost as to what to do next?

Printable View

- Aug 21st 2009, 10:19 AMNotThatGoodJust alittle help
-0.2x^2 + 12x +11 = 0

here is what I have done

-(12) + or - sqrt 12^2-4(-0.2)(11)/2(-0.2)

-12 + or - sqrt 144 +8.8/-0.4

-12 + or - sqrt 152.2/-0.4

at this point I am lost as to what to do next? - Aug 21st 2009, 12:24 PMDefunkt
You are looking to solve this for x, I suppose... If so:

-0.2x^2 + 12x + 11 = 0

x^2 - 60x - 55 = 0

x = ( 60 +- sqrt(3600-4*(-55)) ) / 2

x = ( 60 +- 61.8 ) / 2 -->

x1 = -0.9

x2 = 60.9